MIRCEN electronic network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Biological Nitrogen Fixation Electronic Network (BNFNET) was established in 1990 by the United Nations Educational Social and Cultural Organization's (UNESCO) Microbial Resource Centre (MIRCEN), for laboratories and people who have a...